Reporting Formative Qualitative Research to Support the Development of Quantitative Preference Study Protocols and Corresponding Survey Instruments: Guidelines for Authors and Reviewers - Hollin, Ilene L.; Craig, Benjamin M.; Coast, Joanna; Beusterien, Kathleen; Vass, Caroline; DiSantostefano, Rachael; Peay, Holly (The patient : patient-centered outcomes research, 2020)
Background Formative qualitative research is foundational to the methodological development process of quantitative health preference research (HPR). Despite its ability to improve the validity of the quantitative evidence, formative qualitative research is underreported. Objective To improve the frequency and quality of reporting, we developed guidelines for reporting this type of research. The guidelines focus on formative qualitative research used to develop robust and acceptable quantitative study protocols and corresponding survey instruments in HPR. Methods In December 2018, a steering committee was formed as a means to accumulate the expertise of the HPR community on the reporting guidelines (21 members, seven countries, multiple settings and disciplines). Using existing guidelines and examples, the committee constructed, revised, and refined the guidelines. The guidelines underwent beta testing by three researchers, and further revisions to the guidelines were made based on their feedback as well as on comments from members of the International Academy of Health Preference Research (IAHPR) and the editorial board of The Patient: Patient-Centered Outcomes Research . Results The guidelines have five components: introductory material (4 domains), methods (12), results/findings (2), discussion (2), and other (2). They are concordant with existing guidelines, published examples, beta-testing results, and expert comments. Conclusions Publishing formative qualitative research is a necessary step toward strengthening the foundation of any quantitative study, enhancing the relevance of its preference evidence. The guidelines should aid researchers, reviewers, and regulatory agencies and promote transparency within HPR more broadly.